Modelling and analysis of sensor fault tolerant control using behavioral approach to systems theory - Ng, Peng Hong (2015)
The main focus of this research is to incorporate behavioral approach to systems theory for modelling and analysis of sensor fault tolerant control system (FTCS). The behavioral based approach to systems theory offer a more characteristic or more natural starting point in which the behavior of a system can be defined as the set of all trajectories of the system variables with respect to time according to the mathematical model. Fault related parameters thus can be considered as subsets of the abovementioned trajectories and therefore can be modelled and analysed. Mathematical models of the plants are first derived through the description of the manifest behavior by elimination of the latent variables via a systematic algorithm. Next, the algorithms for obtaining controllers using pole placement techniques are developed based on specified nominal control laws to retain all the desirable trajectories in the plant behavior while rejecting the undesirable ones. State observers are then implemented as the fault detection method in which the discrepancies between the measured values by the sensors and the values of the model are expressed as residuals. The effects of sensor faults in terms of sensor fault scenarios are investigated in the case studies. Finally, the algorithm to obtain a general FTCS framework is developed to provide compensation of the sensor faults through the introduction of a new control law unto the existing nominal one. Results of the case studies showed that performance of the systems can be maintained even in the presence of the sensor faults by incorporating the derived FTCS, most noticeably in the case of total sensors failures. The FTCS is also observed to possess desirable properties including robustness against sensor faults conditions and also sensitive to the disturbance effect.